Second primary malignancies in oral tongue cancer: A Surveillance, Epidemiology, and End Result–based analysis evaluating the basic characteristics, survival outcomes, and predictive factors - Zicheng Xu; Jianxing Wang; Hongzhou Cai; Feng Qi; Qing Zou (Precision Medical Sciences, 2022)
Abstract The purpose of this study is to evaluate the risk of developing a second primary malignancy (SPM) in oral tongue cancer (OTC) patients, and identify the characteristics and survival outcomes of OTC patients with an SPM. Patients with first primary OTC were identified from the Surveillance, Epidemiology, and End Result (SEER) database, and were further divided into the only one primary malignancy (OOPM) group and SPM group. Baseline characteristics and survival outcomes between patients in two groups were compared. Furthermore, a Fine and Gray subdistribution hazard model was utilized to investigate the cumulative risk of developing an SPM in OTC patients. Then, a multivariate competing‐risk model was performed to explore risk predictors. Patients in the SPM group had older age and lower tumor stage than those in the OOPM group. Moreover, the proportion of receiving surgery in the SPM group was significantly higher than that in the OOPM group. Lung was the most common site of SPMs in whole patients. In male patients, the second common site of SPMs was prostate, while in female patients, it was female breast. OTC patients with an SPM of lung and bronchus had the worst overall survival. Finally, older age, male sex, primary site of ventral surface and anterior 2/3 of tongue, localized diseases, and the administration of surgery were considered as risk predictors of developing an SPM in OTC patients. OTC survivors had high risk of developing an SPM, and subsequent malignancy was an important COD. Careful monitoring is warranted in OTC survivors due to the high SPM‐specific mortality.